Innovations in pharmaceutical policies and learnings for sustainable access to affordable medicines - Sabine Vogler; Nina Zimmermann; Manuel Alexander Haasis; Verena Knoll; Jaime Espin; Aukje K. Mantel-Teeuwisse; Dimitra Panteli; Fatima Suleman; Veronika J. Wirtz; Zaheer- (Taylor & Francis Group, 2024)
ABSTRACTSustainable access to affordable medicines remains a public health issue globally, including for high-income countries. To foster the debate on avenues for the future, the fifth PPRI Conference held in Vienna on 25 and 26 April 2024 will offer a forum for the debate on innovating pharmaceutical policymaking to develop and implement futureproof policy options, which are able to address current and future challenges. The Conference invites a broad audience of stakeholders, including researchers, policymakers, payers, patients, industry and health professionals. The conference topics are organised in three strands: Strand 1 on 'Local challenges, global learnings' aims to contribute to lively discussions on the implementation of pharmaceutical policies across the globe. Best-practice examples will be presented, supplemented by case studies of less effective policies which can offer rich learnings. Strand 2 on 'Strengthening the evidence base' is the place for presentations and discussions on topics such as health technology assessments, managed entry agreements and real-world data. Strand 3 'Futureproofing pharmaceutical policies' is particularly dedicated to explore innovation in policymaking to achieve sustainable access to affordable medicines.